The path of man to be actor and the way-round (Olhares, 2015)
This article describes a few experiences developed in LINCE – Laboratory of the Actor in the Departamento de Artes Cênicas from the University of São Paulo. The research has as its scientific object the work of the actor in the scenic practice.
Keywords: Man-actor; Training; Action; Drama school